Compact broadband circularly polarized slot‐patch antenna array. Issue 1 (10th October 2018) - Le, Tuan Tu; Tran, Huy Hung; Nguyen, Truong Khang
Abstract: A simple design of circularly polarized slot‐patch antenna array with broadband operation and compact size is presented in this article. The antenna element consists of a circular slot and a semicircular patch, which are etched on both sides of a substrate. For the gain and axial ratio (AR) bandwidth enhancement, its array antennas are implemented in a 2 × 2 arrangement and fed by a sequential‐phase feeding network. The final 2 × 2 antenna array prototype with compact lateral dimension of 0.8 λ L × 0.8 λ L ( λ L is the lowest frequency within AR bandwidth) yielded a measured impedance bandwidth of 103.83% (2.76‐8.72 GHz) and a measured AR bandwidth of 94.62% (2.45‐6.85 GHz). The peak gain values within the AR bandwidth are from 2.85 to 8.71 dBi. A good agreement between the simulated and measured results is achieved. This antenna array is suitable for multiservice wireless systems covering WiMAX, WLAN and C‐band applications such as satellite communications.